Bioactive semaphorin 3A promotes sequential formation of sensory nerve and type H vessels during in situ osteogenesis - Xiaoxiao Han; Xiaoxiao Han; Yuxuan Ma; Weicheng Lu; Jianfei Yan; Wenpin Qin; Jiaying He; Li-Na Niu; Kai Jiao (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Sensory nerves and vessels are critical for skeletal development and regeneration, but crosstalk between neurovascular network and mineralization are not clear. The aim of this study was to explore neurovascular changes and identify bioactive regulators during in situ osteogenesis.Method:In situ osteogenesis model was performed in male rats following Achilles tenotomy. At 3, 6 and 9 weeks after surgery, mineralization, blood vessels, sensory innervation, and bioactive regulators expression were evaluated via micro-computed tomography, immunofluorescent staining, histology and reverse transcriptase-polymerase chain reaction analyses.Result: In the process of in situ osteogenesis, the mineral density increased with time, and the locations of minerals, nerves and blood vessels were highly correlated at each time point. The highest density of sensory nerve was observed in the experimental group at the 3rd week, and then gradually decreased with time, but still higher than that in the sham control group. Among many regulatory factors, semaphorin 3A (Sema3A) was highly expressed in experimental model and its expression was temporally sequential and spatially correlated sensory nerve.Conclusion: The present study showes that during in situ osteogenesis, innervation and angiogenesis are highly correlated, and Sema3A is associated with the position and expression of the sensory nerve.